Remission in diabetic foot infections: Duration of antibiotic therapy and other possible associated factors. Issue 2 (21st September 2018) - Gariani, Karim; Lebowitz, Dan; von Dach, Elodie; Kressmann, Benjamin; Lipsky, Benjamin A.; Uçkay, Ilker
Abstract : Aim: To determine the most appropriate duration of antibiotic therapy for diabetic foot infections (DFIs). Methods: Using a clinical pathway for adult patients with DFIs (retrospective cohort analysis), we created a cluster‐controlled Cox regression model to assess factors related to remission of infection, emphasizing antibiotic‐related variables. We excluded total amputations as a result of DFI and DFI episodes with a follow‐up time of <2 months. Results: Among 1018 DFI episodes in 482 patients, we identified 392 episodes of osteomyelitis, 626 soft tissue infections, 246 large abscesses, 322 episodes of cellulitis and 335 episodes of necrosis; 313 cases involved revascularization. Patients underwent surgical debridement for 824 episodes (81%), of which 596 (59%) required amputation. The median total duration of antibiotic therapy was 20 days. After a median follow‐up of 3 years, 251 of the episodes (24.7%) were followed by ≥1 additional episode(s). Comparing patients with and without additional episodes, risk of recurrence was lower in those who underwent amputation, had type 1 diabetes, or underwent revascularization. On multivariate analysis including the entire study population, risk of remission was inversely associated with type 1 diabetes (hazard ratio [HR] 0.3, 95% confidence interval [CI] 0.2‐0.6). Neither duration of antibiotic therapy nor parenteral treatment affected risk of recurrence (HR 1.0, 95% CI 0.99‐1.01 for both). Similarly, neither >3 weeks versus <3 weeks of therapy, nor >1 week versus <1 week of intravenous treatment affected recurrence. In stratified analyses for both soft tissue DFIs or osteomyelitis separately, we did not observe associations of antibiotic duration with microbiological or clinical recurrences of DFI. The HRs were 1.0 (95% CI 0.6‐1.8) for an antibiotic duration >3 weeks overall and 0.6 (95% CI 0.2‐1.3) for osteomyelitis cases only. Plotting of duration of antibiotic therapy failed to identify any optimal threshold for preventing recurrences. Conclusions: Our analysis found no threshold for the optimal duration or route of administration of antibiotic therapy to prevent recurrences of DFI. These limited data might support possibly shorter treatment duration for patients with DFI.